STUDY OF EFFECT OF PRE TEACHING TRAINING EXPERIENCE ON STUDENT TEACHERS - Jain, Paras; Parihar, Khusboo Singh (International Journal of Research -GRANTHAALAYAH, 2017)
Pre teaching practice prepares prospective teachers through teaching practice which has an important role to get prior experience of teaching. When the student teachers begin their career with a high self-efficency on the classroom instruction and using the teaching methods, teaching aids they are more concerned, ambitious for their task and work harder. The purpose of this study is to find impact of pre teaching on student teachers in terms of teaching qualities.